Bioeconomies : Life, Technology, and Capital in the 21st Century - Pavone, Vincenzo; Goven, Joanna (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores the promissory discourses and practices associated with the bioeconomy, focusing especially on the transformation of institutions; the creation, appropriation, and distribution of value; the struggle over resources, power, and meaning; and the role of altruism, kinship, and care practices. Governments and science enthusiasts worldwide are embracing the bioeconomy, championing it as the key to health, wealth, and sustainability, while citing it as justification to transform research and regulatory institutions, health and agricultural practices, ethics of privacy and ownership, and conceptions of self and kin. Drawing together studies from Asia, Australia, the Americas, and Europe, this volume encompasses subjects as diverse as regenerative medicine, population health research, agricultural finance, biobanking, assisted reproduction, immigration, breastfeeding, self-help groups, GM fish, and mining sewage.
Keywords: Social sciences.; Management.; Industrial management.; Public policy.; Bioethics.; Philosophy and science.; Life sciences.; elektronické knihy; electronic books